2006
DOI: 10.1210/me.2005-0187
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Inhibitory Polypeptide as an Endogenous Factor Promoting New Bone Formation after Food Ingestion

Abstract: Calcium plays a fundamental role as second messenger in intracellular signaling and bone serves as the body's calcium reserve to tightly maintain blood calcium levels. Calcium in ingested meal is the main supply and inadequate calcium intake causes osteoporosis and bone fracture. Here, we describe a novel mechanism of how ingested calcium is deposited on bone. Meal ingestion elicits secretion of the gut hormone gastric inhibitory polypeptide (GIP) from endocrine K cells in the duodenum. Bone histomorphometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
151
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(160 citation statements)
references
References 29 publications
6
151
2
1
Order By: Relevance
“…This is in contradiction of what was observed in previous studies were these two parameters were increased [13,14]. Connections between fat and bone metabolism have been evidenced, with a role for adipokines in controlling bone remodeling.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…This is in contradiction of what was observed in previous studies were these two parameters were increased [13,14]. Connections between fat and bone metabolism have been evidenced, with a role for adipokines in controlling bone remodeling.…”
Section: Discussioncontrasting
confidence: 92%
“…Furthermore, 6 week-old GIPR-deficient mice did not present with a reduction of the trabecular bone volume. However, the number of osteoclasts was augmented at both ages [13]. On the other hand, using the same GIPR-deficient model, Xie et al described a reduction in trabecular bone volume in younger animals (4-week-old) [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are GIP-specific receptors located on osteoblasts (25) and osteoclasts (26). GIP operates as an anabolic hormone in the bone, where it stimulates incorporation of meal-derived Ca 2+ into bone and bone building (13), and reduces bone absorption by inhibiting osteoclastic activity. Studies in GIPRKO mice have shown that the absence of GIPR signaling leads to significant osteoporosis due to lower osteoblast and higher osteoclast action (13).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its insulinotropic effect, in the absence of which glucose intolerance develops (7), GIP stimulates islet growth (8) and proliferation of b-cells (9), and reduces b-cell apoptosis (10,11). Studies of GIP receptor (GIPR) knock-out (GIPRKO) mice (7) describe GIP as an obesitypromoting factor in high-fat diet (HFD) conditions, and show that deletion of GIPR signaling causes resistance to obesity (12) but leads to osteoporosis (13), revealing an important role of GIP in bone metabolism. However, in these studies, as well as in a model of GIPR antagonism (14), the reported changes were focused on disrupted or blocked GIPR signaling.…”
mentioning
confidence: 99%